SISTEM INFORMASI MANAJEMEN DOKUMEN MENGGUNAKAN METODE PROTOTYPING PADA PT. BANGUN INDAH SAPUTRA - Daffa Bayu Prayoga; Dian Nur Sholihaningtias; Endaryono Endaryono (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
PT. Bangun Indah Saputra is a service company that serves the process of making documents. The purpose of this study is to provide convenience in the management of document maker data. In addition, data security and accuracy are more guaranteed and human resources become more efficient. The research methodology used is Grounded Research method with data collection techniques, namely observation and literature studies that are relevant to the rental system. To build this system is used system design tools that are data flow chart (DAD) context, Zero and detail and by using Java programming language with Netbeans and MySQL database using XAMPP. This system can facilitate the work of the admin in the record so as to increase the effectiveness and consistency of the company PT. Bangun Indah Saputra